2017
DOI: 10.5578/flora.57382
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Virus and Hepatitis E Virus Seroprevalence in Izmir

Abstract: ÖZET Giriş: Genellikle çocukluk çağında görülen hepatit A virüsü (HAV) ve daha çok genç erişkinlerde görülen hepatit E virüsü (HEV) infeksiyonları birçok tropikal ve subtropikal ülkede, özellikle de hijyen koşullarının iyi olmadığı, kişilerin eğitim ve ekonomik düzeylerinin kötü olduğu toplumlarda çeşitli büyüklüklerde epidemiler şeklinde veya sporadik olarak görülür. Bir toplumda hepatit A ve E gibi geniş kitleleri ilgilendiren hastalıklarda koruyucu önlemleri belirlemek için GİRİŞHepatit A virüsü (HAV) ve he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…These seroprevalence results show relatively lower rates when compared with our study. The most recent study with 424 healthy subjects between the ages of 7 and 80 in the central district of Izmir reported HEV seropositivity as 6.6% using Dia.Pro assay . This result is in line with our findings (8.1% by Dia.Pro) considering that no anti‐HEV seropositivity was found in the subgroup aged between 7 and 19, which is probably the reason for the relatively low seroprevalence rate compared with the current study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These seroprevalence results show relatively lower rates when compared with our study. The most recent study with 424 healthy subjects between the ages of 7 and 80 in the central district of Izmir reported HEV seropositivity as 6.6% using Dia.Pro assay . This result is in line with our findings (8.1% by Dia.Pro) considering that no anti‐HEV seropositivity was found in the subgroup aged between 7 and 19, which is probably the reason for the relatively low seroprevalence rate compared with the current study.…”
Section: Discussionsupporting
confidence: 93%
“…In İzmir, the only city from Western Turkey included in this study, 3 HEV seroprevalence studies had so far been performed . In these studies, anti‐HEV seropositivity was reported to be between 3.5% and 7.0%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…HEV IgG positivity rate was 6.6% in 424 healthy people in İzmir. [28] In a study conducted in 180 healthcare workers in our country, anti-HEV IgG was found positive in 13 (7.2%) individuals. [29] It has been reported that HEV exposure is higher in patients with chronic HBV infection than in the general population.…”
Section: Discussionmentioning
confidence: 89%
“…[5] In Turkey, the HEV seroprevalence is 6.3% (range, 0%-34%). [6][7][8][9] There are eight known HEV genotypes; however, only the first four of these genotypes are well-known and cause disease in humans. Genotypes 1 and 2 infect humans through the fecal-oral route and cause outbreaks, particularly in developing countries with poor hygiene conditions.…”
mentioning
confidence: 99%